Photoluminescent Metal–Organic Frameworks – Rapid Preparation, Catalytic Activity, and Framework Relationships. Issue 32 (19th September 2013) - Silva, Patrícia; Ananias, Duarte; Bruno, Sofia M.; Valente, Anabela A.; Carlos, Luís D.; Rocha, João; Almeida Paz, Filipe A.
Abstract: An optimized microwave‐assisted synthesis has been used to prepare an isotypical series of 3D Ln 3+ metal–organic frameworks (MOFs) based on residues of 2, 5‐pyridinedicarboxylic (pydc), namely, [Ln2 (pydc)3 (H2 O)2 ] with Ln 3+ = Ce 3+ (1 ), (La0.95 Eu0.05 ) 3+ (1 ‐LaEu), (La0.95 Tb0.05 ) 3+ (1 ‐LaTb), and (La0.90 Eu0.05 Tb0.05 ) 3+ (1 ‐LaEuTb). The materials can be readily isolated as microcrystals after 1 min of reaction time at 120 °C. The compounds have been extensively studied in the solid state by vibrational spectroscopy (FTIR and FT‐Raman), thermogravimetry, powder X‐ray diffraction, elemental analysis, and electron microscopy (SEM, SEM mapping, and TEM). The structural relationships between the isolated materials and other solids reported in the literature have been investigated in detail from a structural and topological perspective with attention focused on the different connectivities of the employed organic ligand. The 3D densely packed [Ln2 (pydc)3 (H2 O)2 ] compounds are very similar to the previously reported microporous 3D [Ce2 (pydc)2 (Hpydc)(H2 O)2 ]Cl· (9 + y )H2 O; layered [Ce2 (pydc)2 (Hpydc)2 (H2 O)4 · 2H2 O] n can be isolated at lower temperatures and transforms to [Ce2 (pydc)3 (H2 O)2 ] under certain experimental conditions. Compound1 is an effective solid catalyst for the ring opening of styrene with methanol under mild reaction conditions (55 °C) to give 2‐methoxy‐2‐phenylethanol in 100 % selectivity and ca. 80 % conversion. The mixed‐lanthanide materials are effective UV‐to‐visible light converters (red1 ‐LaEu, green1 ‐LaTb, and orange1 ‐LaEuTb). The compounds have very high absolute emission quantum yields (43 % for1 ‐LaEu and 75 % for1 ‐LaTb) under indirect excitation of the UV ligand bands with lifetimes of 0.50 and 1.06 ms for1 ‐LaEu and1 ‐LaTb, respectively, and these properties result from effective intersystem crossing and ligand‐to‐metal transfer processes. Abstract : An optimized microwave‐assisted synthesis was used to prepare [Ln2 (pydc)3 (H2 O)2 ] (pydc = 2, 5‐pyridinedicarboxylic) materials as microcrystals after 1 min of reaction time at 120 °C. The materials are effective solid heterogeneous catalysts and UV‐to‐visible light converters.